2014
DOI: 10.1111/jmft.12061
|View full text |Cite
|
Sign up to set email alerts
|

Individual Therapy for Couple Problems: Perspectives and Pitfalls

Abstract: Despite the demonstrated efficacy of conjoint couple therapy, many clients seeking help for couple problems ultimately find themselves in individual therapy for these concerns. Individual therapy for couple problems (ITCP) may evolve from a partner's refusal of conjoint therapy or from the treatment format preferences of either the client or therapist. Having acknowledged the role of partner refusals, we offer some perspectives about the idiosyncratic personal factors and professional background factors that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…However, previous literature suggests that intervention offered to only one member of a couple, such as individual therapy, is not the most effective treatment to ameliorate severe relationship distress (Atkins, Dimidjian, Bedics, & Christensen, 2009;Emanuels-Zuurveen & Emmelkamp, 1996;Nowlan, Roddy, & Doss, 2017). Traditional individual therapy may hold pitfalls, such as the therapist unknowingly contributing to a further polarization of the couple (Gurman & Burton, 2014). When relationship distress is present in an individual client, engaging a reluctant partner will often be the first priority, except in couples with severe aggression and fear of harm (Halford, Bouma, Kelly, & Young, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous literature suggests that intervention offered to only one member of a couple, such as individual therapy, is not the most effective treatment to ameliorate severe relationship distress (Atkins, Dimidjian, Bedics, & Christensen, 2009;Emanuels-Zuurveen & Emmelkamp, 1996;Nowlan, Roddy, & Doss, 2017). Traditional individual therapy may hold pitfalls, such as the therapist unknowingly contributing to a further polarization of the couple (Gurman & Burton, 2014). When relationship distress is present in an individual client, engaging a reluctant partner will often be the first priority, except in couples with severe aggression and fear of harm (Halford, Bouma, Kelly, & Young, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…IRC makes use of approaches such as behavioural and cognitive behavioural couple therapy, emotion‐focused couple therapy and Gottman Method couple therapy in an individual counselling format to address couple relationship‐focused therapeutic goals, such as setting realistic relationship expectations, positive communication, and conflict management (Gurman & Burton, 2014), and is thus distinct from individual systemic therapies (e.g., structural and strategic family therapy, narrative therapy, solution‐focused therapy). IRC has its unique advantages, including allowing the client to be more open in sharing their feelings and accepting more responsibility for implementing positive behavioural changes in their relationship (Wilson & Flammang, 1990), especially in cases when the other partner is unable to provide support or commit to reducing relationship stress, as in traditional CCT.…”
Section: Predictors Of Positive Therapeutic Outcomementioning
confidence: 99%
“…A number of situations may necessitate the need for IRC. These include but are not limited to a client requesting to be seen alone, a partner’s refusal to be involved in CCT, or a therapist recommending IRC based on the assessment of clients’ circumstances (Gurman & Burton, 2014). Anecdotally, it is common for individuals to attend RC on their own (Bernstein, 2012).…”
Section: Predictors Of Positive Therapeutic Outcomementioning
confidence: 99%
“…Although this couple did well, Feldman's beaten-down husband, who was seen individually, divorced his wife, presumably because he and his individual therapist felt the situation was unworkable. Clinical experience (Graller et al 2001) and formal research (Gurman and Burton 2014) have found that therapists who have not seen the partner (or consulted with someone who has) may too readily conclude that a marriage is hopeless.…”
Section: Rachel and Matt: Pi To Cope With Shamementioning
confidence: 99%